Composite current collector and preparation method and application thereof

By using ethylene-propylene-norbornene polymer base film and performing surface pretreatment, the problem of the composite fluid collector's prone to deformation and insufficient acid-base corrosion resistance at high temperatures is solved, and better high temperature resistance and acid-base corrosion resistance are achieved, and the efficiency of the preparation process and product performance are improved.

CN119890320APending Publication Date: 2025-04-25SHENZHEN SENIOR TECH MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311380835.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing composite liquid collectors are prone to deform, perforated or hot melting at high temperatures, and have insufficient acid and alkali corrosion resistance, which affects their application in vacuum plating equipment and water electroplating tanks.

Method used

The base film of ethylene-propylene-norbornene (EPN) polymer is used as the base film, and the mass percentage content of cycloolefin copolymer and polypropylene is adjusted to improve the high temperature resistance and acid and alkali corrosion resistance of the base film. Meanwhile, surface pretreatment is performed to enhance adhesion between the metal layer and the base film.

Benefits of technology

The high temperature resistance, acid and alkali corrosion resistance and deposition uniformity of the composite fluid collector are significantly improved, the bonding force between the base film and the metal layer is enhanced, and the yield and production efficiency of the preparation process are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004509411050000201
    Figure BDA0004509411050000201
  • Figure BDA0004509411050000211
    Figure BDA0004509411050000211
Patent Text Reader

Abstract

The invention provides a composite current collector and a preparation method and application thereof. The composite current collector comprises an ethylene-propylene-norbornene polymer base film layer and metal layers, wherein the metal layers are respectively arranged on two sides of the ethylene-propylene-norbornene polymer base film layer. The composite current collector provided by the invention has excellent uniformity, stability and conductivity, and also has good high temperature resistance and acid and alkali corrosion resistance, and the yield and production efficiency in the preparation process of the composite current collector are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of current collector materials, and in particular relates to a composite current collector and a preparation method and application thereof. Background Art

[0002] The structure of the composite current collector is similar to a "sandwich", that is, the middle layer is a high molecular polymer base film, and the upper and lower layers are metal-plated layers. The polymer base film has the characteristic of not being easy to break. Even if it breaks, the surface metal layer is thinner than the traditional current collector, and the burrs generated after the break cannot reach the strength to pierce the diaphragm, thereby reducing the risk of the burrs piercing the diaphragm and contacting the electrode. In addition, the traditional current collector can only delay the internal short circuit, and it is at the expense of the battery energy density. The polymer base film in the middle of the composite current collector has flame retardant properties, and its metal conductive layer is thin. It will melt like a fuse when short-circuited, and melt quickly before thermal runaway. The short-circuit current will have a circuit-breaking effect after contacting the polymer base film, so that the battery damage is limited to the puncture site, forming only a "point short circuit".

[0003] However, although the composite current collector disclosed in the prior art has the advantages of greatly improving the safety performance of the battery, reducing its cost and weight, and increasing the energy density, it still has many technical disadvantages in the process of large-scale mass production and application, such as the following aspects: (1) The high temperature resistance of the composite current collector is poor and it is easy to shrink and deform; (2) During the vacuum coating and / or water electroplating process, the corresponding high temperature resistance, acid and alkali corrosion resistance, etc. of conventional polymer-based films such as polyolefins such as polyethylene and polypropylene cannot meet the use requirements, and are prone to problems such as perforation, thermal peeling and shrinkage deformation.

[0004] Therefore, in the art, there is an urgent need to develop a composite current collector to solve the above problems. Summary of the invention

[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a composite current collector and a preparation method and application thereof. In view of the following technical problems existing in the prior art: (1) the composite current collector has poor mechanical properties and is prone to deformation at high temperatures; (2) the metal layer deposition is prone to perforation or thermal melt-through. The composite current collector provided by the present invention has excellent uniformity, stability and electrical conductivity, and at the same time has good high temperature resistance and acid and alkali corrosion resistance. The base film of the metal will not deform or thermally melt-through during the deposition process, which greatly improves the yield and production efficiency in the preparation process of the composite current collector.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a composite current collector, comprising an ethylene-propylene-norbornene polymer base film layer, and metal layers respectively disposed on both sides of the ethylene-propylene-norbornene polymer base film layer.

[0008] First of all, the present invention innovatively proposes for the first time to use ethylene-propylene-norbornene (EPN) polymer base film as the base film, which not only has all the advantages of the original polypropylene resin, but also improves the temperature resistance of the composite current collector by 20°C to 35°C, so that the composite current collector can be used for a long time at a temperature as high as 140°C; at the same time, it has good high temperature resistance and acid and alkali corrosion resistance, and can adapt to the high temperature and high pH environment of the composite current collector during the preparation process, effectively solving the technical problems of poor mechanical strength of the base film of the composite current collector in vacuum plating equipment and water electroplating tanks and easy deformation, perforation or hot melt penetration at high temperature.

[0009] Preferably, the ethylene-propylene-norbornene polymer base film layer is made of cyclic olefin copolymer and polypropylene.

[0010] It should be noted that the glass transition temperature of the cycloolefin copolymer in the present invention is 110°C-178°C, for example, 110°C, 127°C, 130°C, 134°C, 150°C, 170°C, or 178°C.

[0011] Preferably, based on the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 10%-30%, preferably 15%-20%, for example, it can be 10%, 12%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 25%, 28%, 30%, etc.

[0012] In the present invention, by adjusting the mass percentage of the cycloolefin copolymer, the ethylene-propylene-norbornene polymer base film has excellent high temperature resistance and acid and alkali corrosion resistance. If the mass percentage is too low, the high temperature resistance will be poor, and vice versa, the acid and alkali corrosion resistance will be poor.

[0013] Preferably, based on the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the polypropylene is 70%-90%, preferably 80%-85%, for example, it can be 70%, 72%, 75%, 78%, 80%, 81%, 82%, 83%, 84%, 85%, 88%, 90%, etc.

[0014] In the present invention, by adjusting the mass percentage of polypropylene, the ethylene-propylene-norbornene polymer base film has excellent high temperature resistance and acid and alkali corrosion resistance. If the mass percentage is too low, the acid and alkali corrosion resistance will be poor, and vice versa, the high temperature resistance will be poor.

[0015] Preferably, the thickness of the ethylene-propylene-norbornene polymer base film layer is 2-10 μm, for example, 2 μm, 3 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0016] Preferably, the ethylene-propylene-norbornene polymer base film layer needs to be obtained through surface pretreatment.

[0017] In the present invention, the surface pretreatment is to solve the technical problem that the adhesion between the metal layer and the polymer base film layer is poor and easy to fall off. The present invention greatly improves the interfacial bonding force and / or conductivity of the polymer base film by surface pretreatment of the polymer base film, which is conducive to the physical vapor deposition and water electroplating process; in addition, the base film layer and the metal layer in the composite current collector prepared by the present invention are tightly bonded, and the metal layer is evenly distributed and dense, and the internal stress between the metal layers is small, so the prepared composite current collector has excellent deposition uniformity, stability and conductivity.

[0018] Preferably, the cross section of the ethylene-propylene-norbornene polymer-based film layer after surface pretreatment can form a structure including any one of burrs, micropores, a nano-oxide layer or a nano-carbon material layer, or a combination of at least two thereof.

[0019] Preferably, the burrs are uneven protrusions on the cross section of the ethylene-propylene-norbornene polymer base film layer, and the height of the protrusions is less than or equal to 100 nm, for example, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, etc.

[0020] Preferably, the micropores are depressions on the cross section of the ethylene-propylene-norbornene polymer base film layer, and the depth of the depressions is less than or equal to 100 nm, for example, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, etc.

[0021] Preferably, the nano-oxide layer comprises any one of a nano-aluminum oxide layer, a nano-titanium dioxide layer, a nano-zirconium oxide layer, a nano-silicon dioxide layer or a nano-aluminum chromate layer, or a combination of at least two thereof, preferably a nano-aluminum oxide layer and / or a nano-silicon dioxide layer.

[0022] Preferably, the thickness of the nano oxide layer is 0-200 nm, preferably 100-150 nm, for example, it can be 0 nm, 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, etc.

[0023] In the present invention, the interfacial bonding force between the metal layer and the polymer base film is enhanced by adjusting the thickness of the nano oxide layer. If the thickness is too low or too high, the interfacial bonding force cannot be enhanced.

[0024] Preferably, the nano-carbon material layer comprises any one of a nano-conductive carbon black layer, a nano-acetylene black layer, a carbon nanotube layer, a carbon nanofiber layer or a nano-graphene layer, or a combination of at least two thereof, preferably a carbon nanotube layer and / or a nano-graphene layer.

[0025] Preferably, the thickness of the nanocarbon material layer is 0-200nm, preferably 100-150nm, for example, it can be 0nm, 1nm, 2nm, 5nm, 8nm, 10nm, 15nm, 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 150nm, 160nm, 180nm, 200nm, etc.

[0026] In the present invention, by adjusting the thickness of the nano-carbon material layer, the polymer base film has good conductivity, which is beneficial to the deposition and adhesion of the metal layer. If the thickness is too low, the conductivity of the polymer base film cannot be effectively improved, otherwise the metal layer will easily fall off.

[0027] Preferably, the metal element in the metal layer includes any one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten, or a combination of at least two thereof, preferably aluminum and / or copper.

[0028] Preferably, the thickness of the metal layer is 300nm-3000nm, preferably 800-1000nm, for example, it can be 300nm, 500nm, 700nm, 800nm, 900nm, 950nm, 1000nm, 1200nm, 1500nm, 1800nm, 2000nm, 2200nm, 2500nm, 2800nm, 3000nm, etc.

[0029] In the present invention, when the composite current collector is a copper composite current collector, a primer copper layer of a certain thickness is usually deposited on the ethylene-propylene-norbornene polymer base film layer for primer. The primer copper layer is to make the insulating ethylene-propylene-norbornene polymer base film conductive so that it can be electroplated and thickened in the electroplating tank to form a metal layer. The thickness of the primer copper layer is 30-300nm, preferably 30-70nm, for example, 30nm, 40nm, 50nm, 70nm, 100nm, 200nm, 300nm, etc.

[0030] In the present invention, when the composite current collector is an aluminum composite current collector, aluminum cannot be thickened by electroplating and can only be deposited in place in one step by physical vapor deposition technology, so there is no need for a primer setting.

[0031] In a second aspect, the present invention provides a method for preparing the composite current collector according to the first aspect, the method comprising the following steps:

[0032] Metal layers are deposited on both sides of the ethylene-propylene-norbornene polymer base film layer to obtain the composite current collector.

[0033] Preferably, the method for preparing the ethylene-propylene-norbornene polymer base film layer comprises the following steps:

[0034] The cycloolefin copolymer and polypropylene are mixed, and the ethylene-propylene-norbornene polymer base film layer is obtained after vulcanization and hot pressing.

[0035] Preferably, based on the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 10%-30%, preferably 15%-20%, for example, it can be 10%, 12%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 25%, 28%, 30%, etc.

[0036] Preferably, based on the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the polypropylene is 70%-90%, preferably 80%-85%, for example, it can be 70%, 72%, 75%, 78%, 80%, 81%, 82%, 83%, 84%, 85%, 88%, 90%, etc.

[0037] Preferably, the vulcanization temperature is 200° C. and the time is 5 minutes.

[0038] Preferably, the thickness of the ethylene-propylene-norbornene polymer base film layer is 2-10 μm, for example, 2 μm, 3 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0039] Preferably, the ethylene-propylene-norbornene polymer base film layer needs to be obtained through surface pretreatment.

[0040] Preferably, the surface pretreatment method includes any one of vacuum plasma etching technology, deposition technology or surface coating process, or a combination of at least two thereof.

[0041] Preferably, the deposition technique comprises plasma enhanced chemical vapor deposition and / or resistance heating evaporation.

[0042] Preferably, the coating process includes any one of spin coating, spray coating, roller coating, physical vapor deposition or chemical vapor deposition, or a combination of at least two thereof.

[0043] Preferably, the cross section of the ethylene-propylene-norbornene polymer-based film layer after surface pretreatment can form a structure including any one of burrs, micropores, a nano-oxide layer or a nano-carbon material layer, or a combination of at least two thereof.

[0044] Preferably, the burrs are uneven protrusions on the cross section of the ethylene-propylene-norbornene polymer base film layer, and the height of the protrusions is less than or equal to 100 nm.

[0045] Preferably, the micropores are depressions on the cross section of the ethylene-propylene-norbornene polymer-based film layer, and the depth of the depressions is less than or equal to 100 nm.

[0046] Preferably, the nano-oxide layer comprises any one of a nano-aluminum oxide layer, a nano-titanium dioxide layer, a nano-zirconium oxide layer, a nano-silicon dioxide layer or a nano-aluminum chromate layer, or a combination of at least two thereof, preferably a nano-aluminum oxide layer and / or a nano-silicon dioxide layer.

[0047] Preferably, the thickness of the nano oxide layer is 0-200 nm, preferably 100-150 nm, for example, it can be 0 nm, 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, etc.

[0048] In the present invention, the surface pretreatment method of the nano-oxide layer includes plasma enhanced chemical vapor deposition and / or resistance heating evaporation.

[0049] Preferably, the nano-carbon material layer comprises any one of a nano-conductive carbon black layer, a nano-acetylene black layer, a carbon nanotube layer, a carbon nanofiber layer or a nano-graphene layer, or a combination of at least two thereof, preferably a carbon nanotube layer and / or a nano-graphene layer.

[0050] Preferably, the thickness of the nanocarbon material layer is 0-200nm, preferably 100-150nm, for example, it can be 0nm, 1nm, 2nm, 5nm, 8nm, 10nm, 15nm, 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 150nm, 160nm, 180nm, 200nm, etc.

[0051] In the present invention, the surface pretreatment method of the nano-carbon material layer includes any one of spin coating, spray coating, roller coating, physical vapor deposition or chemical vapor deposition, or a combination of at least two of them.

[0052] Preferably, the metal layer is deposited by physical vapor deposition technology.

[0053] Preferably, the physical vapor deposition technology includes any one of magnetron sputtering coating, vacuum sputtering coating, vacuum evaporation coating or vacuum ion coating, or a combination of at least two of them.

[0054] Preferably, the vacuum degree of the magnetron sputtering coating, vacuum sputtering coating, vacuum evaporation coating or vacuum ion coating is 10 -5 -10 -1 Pa, for example, can be 10 -5 Pa, 10 -4 Pa, 10 -3 Pa, 10 -2 Pa, 10 -1 Pa et al.

[0055] In the present invention, by regulating the vacuum degree of magnetron sputtering coating, vacuum sputtering coating, vacuum evaporation coating or vacuum ion coating, metal atoms or ions are uniformly deposited on the surface of the polymer base film. If the vacuum degree is too low, the metal deposition rate and uniformity will be reduced.

[0056] Preferably, the coating rate of the magnetron sputtering coating, vacuum sputtering coating, vacuum evaporation coating or vacuum ion coating is 5m / min-20m / min, for example, it can be 5m / min, 8m / min, 10m / min, 12m / min, 15m / min, 18m / min, 20m / min, etc.

[0057] In the present invention, by regulating the coating rate of magnetron sputtering coating, vacuum sputtering coating, vacuum evaporation coating or vacuum ion coating, metal atoms or ions are uniformly deposited on the surface of the polymer base film. Too low a coating rate will reduce production efficiency, and vice versa, it will cause an uneven metal layer and partial area leakage.

[0058] Preferably, the winding and unwinding tension of the magnetron sputtering coating, vacuum sputtering coating, vacuum evaporation coating or vacuum ion coating is in the range of 80N-120N, for example, it can be 80N, 90N, 100N, 110N, 120N, etc.

[0059] In the present invention, the flatness and integrity of the base film coil are ensured by regulating the winding and unwinding tension of magnetron sputtering coating, vacuum sputtering coating, vacuum evaporation coating or vacuum ion coating. If the winding and unwinding tension is too low, the base film will slip and the coil will deviate. Otherwise, the base film will have wrinkles or even break.

[0060] In the present invention, when the metal layer is aluminum, the physical vapor deposition technology is used to directly form the metal layer; when the metal layer is copper, the physical vapor deposition technology is first used to form the base copper layer, and then the base copper layer is thickened by water electroplating to form the metal layer. Of course, when the metal layer is copper, the physical vapor deposition technology or water electroplating can also be used to directly form the metal layer.

[0061] In the present invention, the water electroplating treatment includes performing water electroplating treatment on both sides of the primer copper layer to obtain the metal layer.

[0062] In the present invention, the water electroplating treatment method includes alkaline ion replacement and / or acidic ion replacement.

[0063] In the present invention, the water electroplating process includes clamping horizontal plating and / or roller horizontal plating.

[0064] The present invention uses ethylene-propylene-norbornene (EPN) polymer base film as the polymer base film, and prepares a composite current collector by combining a physical vapor deposition process and a water electroplating process, so that the composite current collector has excellent uniformity, stability and conductivity. At the same time, the bonding force between the metal layer and the polymer base film is good, and the polymer base film will not be deformed or thermally melted during the metal deposition process, which greatly improves the yield and production efficiency in the preparation process of the composite current collector.

[0065] In a third aspect, the present invention provides an electrode, comprising a current collector and an electrode active material layer disposed on at least one side of the current collector, wherein the current collector comprises the composite current collector according to the first aspect.

[0066] In a fourth aspect, the present invention provides a secondary battery, comprising an electrode, an electrolyte and a separator, wherein the electrode comprises the electrode according to the third aspect.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] Firstly, the present invention innovatively proposes for the first time to use ethylene-propylene-norbornene (EPN) polymer base film as the base film, which not only has all the advantages of the original polypropylene resin, but also improves the temperature resistance of the polymer by 20°C to 35°C, so that the composite current collector can be used for a long time at a temperature as high as 140°C; and can adapt to the high temperature and high pH environment during the preparation of the composite current collector, effectively solving the technical problems of poor mechanical strength of the base film of the composite current collector in vacuum plating equipment and water electroplating tanks and easy deformation, perforation or hot melt penetration at high temperature; secondly, the base film layer and the metal layer in the composite current collector prepared by the present invention are tightly bonded, and the metal layer is evenly distributed and dense, and the internal stress between the metal layers is small, so the prepared composite current collector has excellent deposition uniformity, stability and conductivity. DETAILED DESCRIPTION

[0069] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0070] Example 1

[0071] This embodiment provides a copper composite current collector, which includes an ethylene-propylene-norbornene polymer base film layer with a thickness of 4.5 μm, and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer.

[0072] Among them, the ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene. Taking the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 15%, and the mass percentage of the polypropylene is 85%.

[0073] The method for preparing the ethylene-propylene-norbornene polymer base film comprises the following steps:

[0074] The cycloolefin copolymer and polypropylene in the above formula are mixed, and the ethylene-propylene-norbornene polymer base film is obtained after vulcanization and hot pressing, wherein the vulcanization temperature is 200° C. and the time is 5 minutes.

[0075] This embodiment also provides a method for preparing the copper composite current collector, which comprises the following steps:

[0076] (1) providing an ethylene-propylene-norbornene polymer base film having a thickness of 4.5 μm as a base film;

[0077] (2) Pre-treating the surface of the base film by vacuum plasma etching to improve the roughness and interface bonding strength of the base film;

[0078] (3) depositing a base copper layer on both sides of the surface-treated 4.5 μm ethylene-propylene-norbornene-based film by a magnetron sputtering coating process, wherein the base copper layer on both sides has a thickness of 50 nm and a surface resistance of 1 Ω / □;

[0079] (4) thickening the primer copper layer by a roller-type horizontal plating process, using the double-sided primer copper layer-loaded film obtained in step (3) as a substrate, the substrate as a cathode, and oxygen-free copper as an anode, sequentially through alkaline ion replacement, water washing, acidic ion replacement and anti-oxidation treatment, and depositing electroplated copper layers on both sides of the primer copper layer, respectively, the thickness of the electroplated copper layers on both sides is 950 nm, to obtain a composite copper foil;

[0080] (5) washing, anti-oxidation, drying, rolling and slitting the composite copper foil obtained in step (4) to obtain a copper composite current collector.

[0081] Example 2

[0082] The present embodiment provides a copper composite current collector, which includes an ethylene-propylene-norbornene polymer base film layer with a thickness of 4.5 μm, and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer, and a nano aluminum oxide layer is also formed between the ethylene-propylene-norbornene polymer base film layer and the metal layer.

[0083] Among them, the ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene. Taking the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 15%, and the mass percentage of the polypropylene is 85%.

[0084] The method for preparing the ethylene-propylene-norbornene polymer base film comprises the following steps:

[0085] The cycloolefin copolymer and polypropylene in the above formula are mixed, and the ethylene-propylene-norbornene polymer base film is obtained after vulcanization and hot pressing, wherein the vulcanization temperature is 200° C. and the time is 5 minutes.

[0086] This embodiment also provides a method for preparing the copper composite current collector, which comprises the following steps:

[0087] (1) providing an ethylene-propylene-norbornene polymer base film having a thickness of 4.5 μm as a base film;

[0088] (2) depositing a 100 nm thick aluminum oxide coating on both sides of the base film by physical vapor deposition (PVD) resistance heating deposition process to improve the interfacial bonding strength between the base film and the metal layer;

[0089] (3) depositing a base copper layer on both sides of the surface-treated base film by a magnetron sputtering coating process, wherein the thickness of the base copper layer on both sides is 50 nm and the surface resistance is 1 Ω / □;

[0090] (4) thickening the primer copper layer by a roller-type horizontal plating process, using the double-sided primer copper layer-loaded film obtained in step (3) as a substrate, the substrate as a cathode, and oxygen-free copper as an anode, sequentially through alkaline ion replacement, water washing, acidic ion replacement and anti-oxidation treatment, and depositing electroplated copper layers on both sides of the primer copper layer, respectively, and the thickness of the electroplated copper layers on both sides is 950 nm;

[0091] (5) washing, anti-oxidation, drying, rolling and slitting the composite copper foil obtained in step (4) to obtain a copper composite current collector.

[0092] Example 3

[0093] The present embodiment provides a copper composite current collector, which includes an ethylene-propylene-norbornene polymer base film layer with a thickness of 4.5 μm, and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer, and a nano-silicon dioxide layer is also formed between the ethylene-propylene-norbornene polymer base film layer and the metal layer.

[0094] Among them, the ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene. Taking the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 15%, and the mass percentage of the polypropylene is 85%.

[0095] The method for preparing the ethylene-propylene-norbornene polymer base film comprises the following steps:

[0096] The cycloolefin copolymer and polypropylene in the above formula are mixed, and the ethylene-propylene-norbornene polymer base film is obtained after vulcanization and hot pressing, wherein the vulcanization temperature is 200° C. and the time is 5 minutes.

[0097] This embodiment also provides a method for preparing the copper composite current collector, which comprises the following steps:

[0098] (1) providing an ethylene-propylene-norbornene polymer base film having a thickness of 4.5 μm as a base film;

[0099] (2) a 100 nm thick silicon dioxide coating is deposited on both sides of the base film by plasma enhanced chemical vapor deposition (PECVD) process to improve the interfacial bonding strength between the base film and the metal layer;

[0100] (3) depositing a base copper layer on both sides of the surface-treated base film by a magnetron sputtering coating process, wherein the thickness of the base copper layer on both sides is 50 nm and the surface resistance is 1 Ω / □;

[0101] (4) thickening the primer copper layer by a roller-type horizontal plating process, using the double-sided primer copper layer-loaded film obtained in step (3) as a substrate, the substrate as a cathode, and oxygen-free copper as an anode, sequentially through alkaline ion replacement, water washing, acidic ion replacement and anti-oxidation treatment, and depositing electroplated copper layers on both sides of the primer copper layer, respectively, the thickness of the electroplated copper layers on both sides is 950 nm, to obtain a composite copper foil;

[0102] (5) washing, anti-oxidation, drying, rolling and slitting the composite copper foil obtained in step (4) to obtain a copper composite current collector.

[0103] Example 4

[0104] This embodiment provides a copper composite current collector, which includes an ethylene-propylene-norbornene polymer base film layer with a thickness of 4.5 μm, and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer, and a graphene layer is also formed between the ethylene-propylene-norbornene polymer base film layer and the metal layer.

[0105] Among them, the ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene. Taking the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 15%, and the mass percentage of the polypropylene is 85%.

[0106] The method for preparing the ethylene-propylene-norbornene polymer base film comprises the following steps:

[0107] The cycloolefin copolymer and polypropylene in the above formula are mixed, and the ethylene-propylene-norbornene polymer base film is obtained after vulcanization and hot pressing, wherein the vulcanization temperature is 200° C. and the time is 5 minutes.

[0108] This embodiment also provides a method for preparing the copper composite current collector, which comprises the following steps:

[0109] (1) providing an ethylene-propylene-norbornene polymer base film having a thickness of 4.5 μm as a base film;

[0110] (2) depositing a 100 nm thick graphene coating on both sides of the base film by a roller coating process to improve the conductivity of the base film;

[0111] (3) depositing copper layers on both sides of the base film with the graphene layer on the surface through a roller-type horizontal plating process, wherein the thickness of the electroplated copper layers on both sides is 1000 nm respectively, thereby obtaining a composite copper foil;

[0112] (4) washing, anti-oxidation, drying, rolling and slitting the composite copper foil obtained in step (3) to obtain a copper composite current collector.

[0113] Example 5

[0114] The present embodiment provides a copper composite current collector, which includes an ethylene-propylene-norbornene polymer base film layer with a thickness of 4.5 μm, and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer.

[0115] Among them, the ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene. Taking the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 15%, and the mass percentage of the polypropylene is 85%.

[0116] The method for preparing the ethylene-propylene-norbornene polymer base film comprises the following steps:

[0117] The cycloolefin copolymer and polypropylene in the above formula are mixed, and the ethylene-propylene-norbornene polymer base film is obtained after vulcanization and hot pressing, wherein the vulcanization temperature is 200° C. and the time is 5 minutes.

[0118] This embodiment also provides a method for preparing the copper composite current collector, which comprises the following steps:

[0119] (1) providing an ethylene-propylene-norbornene polymer base film having a thickness of 4.5 μm as a base film;

[0120] (2) performing vacuum plasma etching surface pretreatment on both sides of the base film to improve the roughness and interface bonding strength of the base film;

[0121] (3) depositing a base copper layer on both sides of the surface-treated base film by a magnetron sputtering coating process, wherein the thickness of the base copper layer on both sides is 50 nm and the surface resistance is 1 Ω / □;

[0122] (4) A metal copper layer is continuously deposited on the surface of the magnetron sputtered primer copper layer by vacuum evaporation coating process, and the thickness of the metal copper layer deposited on both sides by vacuum evaporation coating process is 50 nm respectively, and the surface resistance is 300 mΩ / □;

[0123] (5) thickening the primer copper layer by a roller-type horizontal plating process, using the film with primer copper layers on both sides obtained in step (4) as a substrate, the substrate as a cathode, and oxygen-free copper as an anode, sequentially through alkaline ion replacement, water washing, acidic ion replacement and anti-oxidation treatment, and depositing electroplated copper layers on the primer copper layers on both sides, respectively, the thickness of the electroplated copper layers on both sides is 900 nm, to obtain a composite copper foil;

[0124] (6) washing, anti-oxidation, drying, rolling and slitting the composite copper foil obtained in step (5) to obtain a copper composite current collector.

[0125] Example 6

[0126] This embodiment provides an aluminum composite current collector, which includes an ethylene-propylene-norbornene polymer base film layer with a thickness of 4.5 μm, and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer, and a nano aluminum oxide layer is also formed between the ethylene-propylene-norbornene polymer base film layer and the metal layer.

[0127] Among them, the ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene. Taking the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 15%, and the mass percentage of the polypropylene is 85%.

[0128] The method for preparing the ethylene-propylene-norbornene polymer base film comprises the following steps:

[0129] The cycloolefin copolymer and polypropylene in the above formula are mixed, and the ethylene-propylene-norbornene polymer base film is obtained after vulcanization and hot pressing, wherein the vulcanization temperature is 200° C. and the time is 5 minutes.

[0130] This embodiment also provides a method for preparing the aluminum composite current collector, which comprises the following steps:

[0131] (1) providing an ethylene-propylene-norbornene polymer base film having a thickness of 4.5 μm as a base film;

[0132] (2) depositing a 100 nm thick aluminum oxide coating on both sides of the base film by physical vapor deposition (PVD) resistance heating deposition process to improve the interfacial bonding strength between the base film and the metal layer;

[0133] (3) depositing a metal aluminum layer on both sides of the surface-treated base film through a vacuum evaporation process, wherein the thickness of the metal aluminum layer on both sides is 1000 nm respectively, thereby obtaining a composite aluminum foil;

[0134] (4) The composite aluminum foil obtained in step (3) is rolled up and slit to obtain an aluminum composite current collector.

[0135] Example 7

[0136] This embodiment provides an aluminum composite current collector, which includes an ethylene-propylene-norbornene polymer base film layer with a thickness of 4.5 μm, and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer, and a nano-silicon dioxide layer is also formed between the ethylene-propylene-norbornene polymer base film layer and the metal layer.

[0137] Among them, the ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene. Taking the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 15%, and the mass percentage of the polypropylene is 85%.

[0138] The method for preparing the ethylene-propylene-norbornene polymer base film comprises the following steps:

[0139] The cycloolefin copolymer and polypropylene in the above formula are mixed, and the ethylene-propylene-norbornene polymer base film is obtained after vulcanization and hot pressing, wherein the vulcanization temperature is 200° C. and the time is 5 minutes.

[0140] This embodiment also provides a method for preparing the above-mentioned composite current collector, which comprises the following steps:

[0141] (1) providing an ethylene-propylene-norbornene polymer base film having a thickness of 4.5 μm as a base film;

[0142] (2) a 100 nm thick silicon dioxide coating is deposited on both sides of the base film by plasma enhanced chemical vapor deposition (PECVD) to improve the interfacial bonding strength between the base film and the metal layer;

[0143] (3) depositing a metal aluminum layer on both sides of the surface-treated base film through a vacuum evaporation process, wherein the thickness of the metal aluminum layer on both sides is 1000 nm respectively, thereby obtaining a composite aluminum foil;

[0144] (4) The composite aluminum foil obtained in step (3) is rolled up and slit to obtain an aluminum composite current collector.

[0145] Example 8

[0146] This embodiment provides an aluminum composite current collector, which includes an ethylene-propylene-norbornene polymer base film layer with a thickness of 4.5 μm, and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer.

[0147] Among them, the ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene. Taking the total mass of the ethylene-propylene-norbornene polymer base film layer as 100%, the mass percentage of the cycloolefin copolymer is 15%, and the mass percentage of the polypropylene is 85%.

[0148] The method for preparing the ethylene-propylene-norbornene polymer base film comprises the following steps:

[0149] The cycloolefin copolymer and polypropylene in the above formula are mixed, and the ethylene-propylene-norbornene polymer base film is obtained after vulcanization and hot pressing, wherein the vulcanization temperature is 200° C. and the time is 5 minutes.

[0150] This embodiment also provides a method for preparing the aluminum composite current collector, which comprises the following steps:

[0151] (1) providing an ethylene-propylene-norbornene polymer base film having a thickness of 4.5 μm as a base film;

[0152] (2) vacuum plasma etching is performed on both sides of the polymer base film to pre-treat the surface to improve the roughness and interface bonding strength of the base film;

[0153] (3) depositing a metal aluminum layer on both sides of the surface-treated base film by a magnetron evaporation process, wherein the thickness of the metal aluminum layer on both sides is 1000 nm;

[0154] (4) Rolling and slitting are performed to obtain an aluminum composite current collector.

[0155] Example 9

[0156] The difference between this embodiment and embodiment 1 is that, based on the total mass of the ethylene-propylene-norbornene polymer base film layer being 100%, the mass percentage of the cycloolefin copolymer is 20%, and the mass percentage of the polypropylene is 80%. The rest is the same as embodiment 1.

[0157] Example 10

[0158] The difference between this embodiment and embodiment 1 is that, based on the total mass of the ethylene-propylene-norbornene polymer base film layer being 100%, the mass percentage of the cycloolefin copolymer is 10%, and the mass percentage of the polypropylene is 90%, and the rest is the same as embodiment 1.

[0159] Embodiment 11

[0160] The difference between this embodiment and embodiment 1 is that the thickness of the ethylene-propylene-norbornene polymer base film used is 2 μm, and the other aspects are the same as those of embodiment 1.

[0161] Example 12

[0162] The difference between this embodiment and embodiment 1 is that the thickness of the ethylene-propylene-norbornene polymer base film used is 10 μm, and the other aspects are the same as those of embodiment 1.

[0163] Example 13

[0164] The difference between this embodiment and embodiment 8 is that, based on the total mass of the ethylene-propylene-norbornene polymer base film layer being 100%, the mass percentage of the cycloolefin copolymer is 20%, and the mass percentage of the polypropylene is 80%, and the rest is the same as embodiment 8.

[0165] Embodiment 14

[0166] The difference between this embodiment and embodiment 8 is that the thickness of the ethylene-propylene-norbornene polymer base film used is 2 μm, and the other aspects are the same as those of embodiment 8.

[0167] Embodiment 15

[0168] The difference between this embodiment and embodiment 8 is that the thickness of the ethylene-propylene-norbornene polymer base film used is 10 μm, and the other aspects are the same as those of embodiment 8.

[0169] Example 16

[0170] The difference between this embodiment and embodiment 1 is that the ethylene-propylene-norbornene polymer base film is not subjected to any surface treatment, and the rest is the same as embodiment 1.

[0171] Embodiment 17

[0172] The difference between this embodiment and embodiment 8 is that the ethylene-propylene-norbornene polymer base film is not subjected to any surface treatment, and the rest is the same as embodiment 8.

[0173] Comparative Example 1

[0174] This comparative example provides a copper composite current collector, which includes a polypropylene base film with a thickness of 4.5 μm, and metal copper layers with a thickness of 1000 nm are respectively arranged on both sides of the polypropylene base film, and the base film is not subjected to any surface treatment.

[0175] Comparative Example 2

[0176] This comparative example provides an aluminum composite current collector, which includes a polypropylene base film with a thickness of 10 μm, and metal aluminum layers with a thickness of 1000 nm are respectively arranged on both sides of the polypropylene base film, and the base film is not subjected to any surface treatment.

[0177] Comparative Example 3

[0178] The difference between this embodiment and embodiment 1 is that the 4.5 μm ethylene-propylene-norbornene polymer base film layer is replaced with a 4.5 μm polypropylene base film, and the rest is the same as embodiment 1.

[0179] Comparative Example 4

[0180] The difference between this embodiment and embodiment 2 is that the 4.5 μm ethylene-propylene-norbornene polymer base film layer is replaced with a 4.5 μm polypropylene base film, and the rest is the same as embodiment 2.

[0181] Test conditions

[0182] The composite current collectors provided in Examples 1 to 17 and Comparative Examples 1 to 4 were tested, and the testing method was as follows:

[0183] The microstructure was observed and analyzed by high-magnification scanning electron microscope.

[0184] The thickness of the metal layer was measured using a German Mahr thickness gauge (model: C1216) at least 10 points along the TD direction of the composite current collector, and the average value was taken as the thickness of the metal layer.

[0185] The surface square resistance was tested using a four-probe resistance tester at five locations around and in the center of the composite current collector, and the average value was taken.

[0186] The high temperature test is to keep the composite current collector in an oven at 150±5℃ for 24h, and observe the deformation degree of the composite current collector and the peeling of the metal layer. The sum of the length change rate of the composite current collector in the TD direction and the length change rate in the MD direction is set as the deformation degree. If the deformation degree of the composite current collector is ≤10% and there is no peeling of the metal layer, it passes the high temperature test, otherwise it fails.

[0187] The acid and alkali resistance test is to completely immerse the composite current collector sample in 5% sulfuric acid or sodium hydroxide solution for 24 hours at room temperature and pressure, and observe the expansion, peeling, corrosion, and shedding of the sample. The sum of the length change rate of the composite current collector in the TD direction and the length change rate in the MD direction is set as the deformation degree. If the deformation degree of the composite current collector is ≤10%, there is no corrosion, and no metal layer falls off, it is considered to have passed the acid and alkali resistance test, otherwise it is considered to have failed.

[0188] The peel strength was tested on a universal tensile testing machine and analyzed according to the national standard GB / T 2792-2014.

[0189] The puncture resistance strength was measured using a puncture tester (model: CMT8102) produced by Meters Industrial Systems (China) Co., Ltd. The specimen clamp opening diameter was about 12 mm, the needle tip curvature radius was 0.5 mm, the temperature was 22-24°C, and the puncture speed was 5 mm / sec.

[0190] The tensile strength and elongation at break were tested on a tensile testing machine (model: EM6.202) of MTS Industrial Systems (China) Co., Ltd. in accordance with the national standard GB / T 16492-2008. The greater the elongation at break, the less likely the composite current collector is to be broken and the better the extensibility.

[0191] The test results are shown in Table 1:

[0192] Table 1

[0193]

[0194]

[0195] It can be seen from Examples 16-17 and Comparative Examples 1-2 that, compared with the traditional polypropylene-based film, the present invention regulates the type of polymer-based film and the corresponding composition, so that the provided ethylene-propylene-norbornene polymer-based film composite current collector has better high temperature resistance and acid and alkali corrosion resistance, and the mechanical properties of the prepared composite current collector, such as peel strength, puncture resistance, tensile strength and elongation at break, are significantly better, and the surface resistance is also lower.

[0196] With reference to Examples 1-15 and Examples 16-17, it can be seen that after the ethylene-propylene-norbornene polymer base film is surface treated, the peel strength performance of the prepared composite current collector is significantly better, thereby improving the processing performance of the electrode sheet and the safety of the lithium-ion battery in subsequent applications.

[0197] It can be seen from Examples 1-2 and Comparative Examples 3-4 that, compared with the traditional polypropylene-based film, the present invention regulates the type and corresponding composition of the polymer-based film so that the provided ethylene-propylene-norbornene polymer-based film composite current collector has better high temperature resistance and acid and alkali corrosion resistance, and the mechanical properties of the prepared composite current collector, such as puncture resistance, tensile strength and elongation at break, are significantly better.

[0198] In summary, compared with the traditional polypropylene-based film, the present invention regulates the type and corresponding composition of the polymer-based film, and uses surface pretreatment to modify it, so that the provided ethylene-propylene-norbornene polymer-based film composite current collector has better high temperature resistance and acid and alkali corrosion resistance; and after the polymer-based film is surface treated, the mechanical properties of the prepared composite current collector, such as peel strength, puncture resistance, tensile strength and elongation at break, are significantly better, thereby improving the processing performance of the electrode sheet and the safety of the lithium-ion battery in subsequent applications. The composite current collector prepared by the process of the present invention has a more uniform, continuous and dense microscopic morphology, which is conducive to improving the adhesion and conductivity of the metal layer, thereby improving the cycle life of the lithium-ion battery.

[0199] And it was found in the manufacturing process that the yield rate of the composite current collector obtained in Comparative Examples 1-4 was lower than that of the composite current collector obtained in Example 1-17, and the yield rate of the composite current collector obtained in Comparative Examples 1-4 was about 20% lower than that of the composite current collector obtained in Comparative Examples 1-17. This is because in the manufacturing process of Comparative Examples 1-4, the base film will be greatly deformed or thermally melted during the step of depositing the metal layer, resulting in a decrease in the yield rate.

[0200] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite current collector, characterized in that: The composite current collector comprises an ethylene-propylene-norbornene polymer base film layer and metal layers respectively arranged on both sides of the ethylene-propylene-norbornene polymer base film layer.

2. The composite current collector according to claim 1, characterized in that: The ethylene-propylene-norbornene polymer base film layer is made of cycloolefin copolymer and polypropylene; Preferably, based on the total mass of the ethylene-propylene-norbornene polymer base film layer being 100%, the mass percentage of the cycloolefin copolymer is 10%-30%, preferably 15%-20%; Preferably, based on the total mass of the ethylene-propylene-norbornene polymer-based film layer being 100%, the mass percentage of the polypropylene is 70%-90%, preferably 80%-85%.

3. The composite current collector according to claim 1 or 2, characterized in that: The thickness of the ethylene-propylene-norbornene polymer base film layer is 2-10 μm.

4. The composite current collector according to any one of claims 1 to 3, characterized in that: The ethylene-propylene-norbornene polymer base film layer needs to be obtained through surface pretreatment; Preferably, the cross section of the ethylene-propylene-norbornene polymer-based film layer after surface pretreatment can form a structure including any one of burrs, micropores, a nano-oxide layer or a nano-carbon material layer, or a combination of at least two thereof; Preferably, the burr is an uneven protrusion on the cross section of the ethylene-propylene-norbornene polymer base film layer, and the height of the protrusion is less than or equal to 100 nm; Preferably, the micropores are depressions on the cross section of the ethylene-propylene-norbornene polymer base film layer, and the depth of the depressions is less than or equal to 100 nm; Preferably, the nano-oxide layer comprises any one of a nano-aluminum oxide layer, a nano-titanium dioxide layer, a nano-zirconium oxide layer, a nano-silicon dioxide layer or a nano-aluminum chromate layer, or a combination of at least two thereof, preferably a nano-aluminum oxide layer and / or a nano-silicon dioxide layer; Preferably, the thickness of the nano-oxide layer is 0-200 nm, preferably 100-150 nm; Preferably, the nano-carbon material layer comprises any one of a nano-conductive carbon black layer, a nano-acetylene black layer, a carbon nanotube layer, a carbon nanofiber layer or a nano-graphene layer, or a combination of at least two thereof, preferably a carbon nanotube layer and / or a nano-graphene layer; Preferably, the thickness of the nano-carbon material layer is 0-200 nm, preferably 100-150 nm.

5. The composite current collector according to any one of claims 1 to 4, characterized in that: The metal element in the metal layer includes any one or a combination of at least two of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten, preferably aluminum and / or copper; Preferably, the thickness of the metal layer is 300-3000 nm, preferably 800-1000 nm.

6. A method for preparing a composite current collector according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: Metal layers are deposited on both sides of the ethylene-propylene-norbornene polymer base film layer to obtain the composite current collector.

7. The method according to claim 6, characterized in that The method for preparing the ethylene-propylene-norbornene polymer base film layer comprises the following steps: The cycloolefin copolymer and polypropylene are mixed, and the ethylene-propylene-norbornene polymer base film layer is obtained after vulcanization and hot pressing; Preferably, based on the total mass of the ethylene-propylene-norbornene polymer base film layer being 100%, the mass percentage of the cycloolefin copolymer is 10%-30%, preferably 15%-20%; Preferably, based on the total mass of the ethylene-propylene-norbornene polymer base film layer being 100%, the mass percentage of the polypropylene is 70%-90%, preferably 80%-85%; Preferably, the vulcanization temperature is 200°C and the time is 5 minutes; Preferably, the thickness of the ethylene-propylene-norbornene polymer base film layer is 2-10 μm.

8. The method according to claim 6 or 7, characterized in that: The ethylene-propylene-norbornene polymer base film layer needs to be obtained through surface pretreatment; Preferably, the surface pretreatment method includes any one or a combination of at least two of vacuum plasma etching technology, deposition technology or surface coating technology; Preferably, the deposition technique comprises plasma enhanced chemical vapor deposition and / or resistance heating evaporation; Preferably, the coating process comprises any one or a combination of at least two of spin coating, spray coating, roller coating, physical vapor deposition or chemical vapor deposition; Preferably, the cross section of the ethylene-propylene-norbornene polymer-based film layer after surface pretreatment can form a structure including any one of burrs, micropores, a nano-oxide layer or a nano-carbon material layer, or a combination of at least two thereof; Preferably, the burr is an uneven protrusion on the cross section of the ethylene-propylene-norbornene polymer base film layer, and the height of the protrusion is less than or equal to 100 nm; Preferably, the micropores are depressions on the cross section of the ethylene-propylene-norbornene polymer base film layer, and the depth of the depressions is less than or equal to 100 nm; Preferably, the nano-oxide layer comprises any one of a nano-aluminum oxide layer, a nano-titanium dioxide layer, a nano-zirconium oxide layer, a nano-silicon dioxide layer or a nano-aluminum chromate layer, or a combination of at least two thereof, preferably a nano-aluminum oxide layer and / or a nano-silicon dioxide layer; Preferably, the thickness of the nano-oxide layer is 0-200 nm, preferably 100-150 nm; Preferably, the nano-carbon material layer comprises any one of a nano-conductive carbon black layer, a nano-acetylene black layer, a carbon nanotube layer, a carbon nanofiber layer or a nano-graphene layer, or a combination of at least two thereof, preferably a carbon nanotube layer and / or a nano-graphene layer; Preferably, the thickness of the nano-carbon material layer is 0-200 nm, preferably 100-150 nm; Preferably, the deposition method of the metal layer is physical vapor deposition technology; Preferably, the physical vapor deposition technology includes any one of magnetron sputtering coating, vacuum sputtering coating, vacuum evaporation coating or vacuum ion coating, or a combination of at least two of them.

9. An electrode, characterized in that: The electrode comprises a current collector and an electrode active material layer disposed on at least one side of the current collector, and the current collector comprises the composite current collector according to any one of claims 1 to 5.

10. A secondary battery, characterized in that: The secondary battery includes an electrode, an electrolyte, and a separator, and the electrode includes the electrode according to claim 9.